2020
DOI: 10.3390/su12072608
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Decision for Supply Chain with Corporate Social Responsibility and Lag Effect

Abstract: With the deepening of economic globalization and international division of labor, enterprises gradually turn to supply chain management methods that aiming at win-win cooperation. An enterprise’s corporate social responsibility (CSR) behaviors will affect the interests of other enterprises in the supply chain through transmission, diffusion, amplification, feedback, etc. Therefore, scholars are currently focusing on helping supply chain enterprises to take social responsibility. This paper takes a two-echelon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Return on assets (ROA) is a commonly used indicator of financial performance (Godos-Dı´ez et al, 2014). Previous studies have shown that the effect of antecedents on CSR often has a time lag effect (Cheng & Ding, 2020). Therefore, in addition to the current ROA (ROA in 2018), because of possible endogenous issues, we also use the 1-year lag of ROA (ROAFL), 2-year lag of ROA (ROASL), and 3-year lag of ROA (ROATL) as independent variables, separately.…”
Section: Variables Measurementmentioning
confidence: 99%
“…Return on assets (ROA) is a commonly used indicator of financial performance (Godos-Dı´ez et al, 2014). Previous studies have shown that the effect of antecedents on CSR often has a time lag effect (Cheng & Ding, 2020). Therefore, in addition to the current ROA (ROA in 2018), because of possible endogenous issues, we also use the 1-year lag of ROA (ROAFL), 2-year lag of ROA (ROASL), and 3-year lag of ROA (ROATL) as independent variables, separately.…”
Section: Variables Measurementmentioning
confidence: 99%
“…CSR can consider not only the development of individual enterprises but also the realisation of CSR in the entire supply chain (Bhardwaj, 2016). Cheng and Ding (2020) believe that, in an increasingly competitive environment, the supply chain model has become the mainstream mode of sustainable development of enterprises. Li (2020) studied the impact of credit support, government subsidies and internal cost subsidies on supply chain CSR decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies on supply chain CSR mainly concentrated on the following three aspects. Debates were proposed on how to promote CSR among different types of supply chain enterprises, such as two‐echelon supply chain (Cheng & Ding, 2020; Jokar & Hosseini‐Motlagh, 2020; Panda et al, 2017; Wang, 2020), three‐echelon supply chain (Hosseini‐Motlagh, Govindan, et al, 2019), closed‐loop supply chain (Modak et al, 2019; Modak & Kelle, 2019; Wang et al, 2021), dual‐channel supply chain (Hosseini‐Motlagh, Nouri‐Harzvili, et al, 2019; Li et al, 2020) and green supply chain (Huang et al, 2021; Wang, Wang, & Zhang, 2020). For example, Asif et al (2013) presented a framework that can help the effective integration of CSR and existing business processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate social responsibility (CSR) construction is essential for supply chains, enterprises, and society (Cheng & Ding, 2020; Fontoura & Coelho, 2021; Lee & Jung, 2016), because how enterprises actively shoulder social responsibility is related to the development of the national economy (McWilliams & Siegel, 2001). As the performance of one‐time high‐input CSR projects is usually lower than that of continuous medium‐to‐long term CSR projects under the same cost (Hollingworth & Valentine, 2014), it is more valuable from a long‐term perspective.…”
Section: Introductionmentioning
confidence: 99%